Aerospace series. Cables, electrical, for general purpose, single and multicore assembly. XLETFE Family. Jacketed or screened and jacketed. Nickel plated copper. Operating temperatures, between - 65 °C and 150 °C. Dual extruded wall for open applications, with jacket without screen. UV laser printable. Product standard Part 011, (6th September 2019) - British Standards Institution,
No abstract available